ARC/ARG3.1 binds the nuclear polyadenylate-binding protein RRM and regulates neuronal activity-dependent formation of nuclear speckles - Tambudzai Kanhema; Kamil Parobczak; Sudarshan Patil; Dagmara Holm-Kaczmarek; Erik I. Hallin; Jan Ludwiczak; Andrzej Antoni Szczepankiewicz; Francois Philippe Pauzin; Aamra Mahboob; Adrian Szum; Yuta Ishizuka; Stanisław Dunin-Horkawicz; et al. (Cell Reports)
Summary: ARC is a neuronal activity-induced protein interaction hub with critical roles in synaptic plasticity and memory. ARC localizes to synapses and the nucleus, but its nuclear functions are little known. Following in vivo long-term potentiation (LTP) induction in the dentate gyrus, we show that ARC accumulates in the nucleosol fraction and interchromatin space of granule cells. Proteomic analysis of immunoprecipitated ARC complexes identifies proteins involved in pre-mRNA processing. We demonstrate endogenous ARC protein-protein interaction with polyadenylate-binding nuclear protein 1 (PABPN1) and the paraspeckles protein polypyrimidine tract-binding protein (PTB)-associated splicing factor (PSF). In vitro peptide binding arrays show direct binding of purified ARC to the PABPN1 poly(A)-RNA recognition motif. 3D morphometric imaging reveals structural changes in PABPN1 foci corresponding to classical nuclear speckles following in vivo and in vitro LTP. Depletion of ARC disrupts the maintenance and activity-dependent formation of PABPN1 speckles, thus implicating ARC in regulation of nuclear speckle dynamics and pre-mRNA processing.